Pendugaan Sebaran Klorofil-A dan Suhu Permukaan Air Laut untuk Menentukan Fishing Ground dengan Menggunakan Teknologi Pengindraan Jauh di Perairan Pantai Barat Sulawesi Selatan - Asmidar, Asmidar; Danial, Danial; Rismang, Rismang (Program Studi Ilmu Kelautan Fakuktas Ilmu Perikanan dan Kelautan Universitas Muslim Indonesia, 2023)
Estimation of Chlorophyll-A Distribution and Sea Surface Temperature to Determine Fishing Ground Areas Using Remote Sensing Technology in West Coast Waters of South Sulawesi. The aim of this research is to study the distribution patterns of Chlorophyll-a and Sea Surface Temperature, and their relationship with potential fishing ground areas in the waters. West coast of South Sulawesi by utilizing Remote Sensing technology. The methodology used includes several stages, namely data collection of fashionable oceancolor 8 Day Chlorophyill Concentration and 8 Day Surface Temperature level 3 satellite imagery data with a resolution of 9 km, which is then carried out further processing using mapping software. The implementation of this research took place on May 1, 2015 until June 30 2015. The results of the study showed that in May - June 2015 there was a decrease in sea surface temperature of 1.35°C where the monthly average sea surface temperature ranged from 26.72° - 31.16°C. Sea Surface Temperature was relatively high in the first week of May 2015 compared to the following weeks during May – June. Chlorophyll-a concentration in the study area ranged from 0.06 – 3.34 mg/m³ based on the average. The relatively high concentration of Chlorophyll-a occurred on the second week of June 2015. The most potential Fishing Ground area was in June 2015 with the coordinates of 117° West – 119.5° East with a temperature range ranging from 27.06° – 29.04° C and 0.2 – 0.28 mg/m³ for the range of Chlorophyll-a concentrations.